Implementation of dose calculation methods for NORM by-products in building materials in the circular economy framework - La Verde, Giuseppe; Gagliardo, Gaetano; Ambrosino, Fabrizio; Pugliese, Mariagabriella (Frontiers in Built Environment, 2024)
Introduction: Risk assessment of exposure to indoor pollutants plays an increasingly important role in human protection, and one of the main sources of indoor pollutants is building materials (BMs). In addition, production processes, including those related to BMs, are also involved in economic transition: the use of by-products from other industrial sectors as raw materials for the production processes in compliance with environmental sustainability is evaluated. Methods: In this work, we evaluate not only the radiation protection of BMs but also the possibility of adopting the circular economy principles. The two main objectives of this study were 1) radiometric characterization and calculation of Index I of pozzolan from Altavilla Irpina (Avellino) in Italy, used as a natural igneous additive for concrete, using gamma spectroscopy, and 2) comparison of different methodologies for calculating the annual effective dose of BMs (CEN/TR 17113:2017, RESRAD-BUILD software, and a previously developed experimental method). The same approach was extended to the possibility of reusing fly ash—a naturally occurring radioactive material (NORM) by-product of coal combustion in thermal power plants—for the production of concrete. Results and Discussion: The study aligns with the principles linked to the circular economy to extend the life cycle of materials by reducing the need for natural resources, suggesting a possible positive compromise between radioprotection and preservation of environmental heritage.